BOOK REVIEWS (Journal of Finance, 1977)
Book reviewed in this article: Introduction to Money and Banking . By R ichard S. T horn . Management of Bank Portfolios . By S tephen P. B radley and D wight B. C rane . The Principles of Monetary Economics . By J ames M. B oughton and E lmus R. W icker . Selective Credit Controls in Western Europe . By D onald H odgman . Financial Statement Analysis: A New Approach . By B aruch L ev . Foundations of Finance . By E ugene F. F ama . Investment Analysis and Securities Markets . By M orris M endelson and S idney R obbins . National Health Insurance: Benefits, Costs and Consequences . By K aren D avis .